Parental mental health care after their child’s pediatric intensive care hospitalization - Logan, Grace E. (Pediatr Crit Care Med, 2020)
OBJECTIVE: Post-traumatic stress disorder (PTSD), depression and anxiety have all been found in parents of PICU survivors. How these research findings translate to actual use of mental health services by parents remains unknown. DESIGN: Retrospective observational cohort study. SETTING: Insurance claims data from 2006-2013 obtained from the IBM® MarketScan® Commercial Database. PATIENTS: Parents of PICU survivors. INTERVENTIONS, MEASUREMENTS, AND MAIN RESULTS: We examined rates of 1) mental health diagnoses, 2) outpatient mental health visits, and 3) prescriptions for antidepressants and anxiolytics among parents, 6 months before and 6 months after their child’s PICU admission, using each parent as their own control. Of the 95,070 parents identified, 9.5% received a new mental health diagnosis in the 6 months after their child’s PICU hospitalization, which represented a 110% increase from pre-PICU rates. A smaller proportion of parents were given new prescriptions for antidepressants (3.4%) and anxiolytics (3.9%) in the 6 months after their child’s PICU hospitalization. Mothers were twice as likely to receive a new mental health diagnosis and be taking a new medication than fathers in the post-PICU period. The parental diagnosis of acute stress disorder or PTSD increased by 87% from the pre-PICU to the post-PICU period. CONCLUSIONS: After their child’s PICU hospitalization, the proportion of parents with a new mental health diagnosis nearly doubled. Mothers were at nearly twice the risk of receiving a new mental health diagnosis and receiving a new mental health medication compared to fathers. The proportion of parents receiving mental health care is much lower than the proportion reporting mental health symptoms in long-term outcomes studies. Whether this indicates a gap in health care delivery for parents with mental health symptoms remains unknown.